Use of computer resources in electromagnetics classes: a teaching sequence - Lanfranco, Áurea C.P. Marcelino; Teixeira, Jonny Nelson; Camargo, Leiana (Revista Hipótese, 2020)
The objective of this research is to present a didactic sequence that was developed in a public school in São Paulo with students from the 3rd year of EM. The classes were planned using computational resources through a didactic sequence. The developed activities followed a logic and is shown to be effective, because, at the end of the sequence approached, the objectives were achieved, it is evident that using computational resources in bimonthly / semester planning makes the classes more interesting, clearly shows the physical concepts that one wants. work and the cost is not high because the key is to adapt the resources available at school.
Keywords: Teaching; Physical; TDIC; Sequence; Didactics